Shrimp production and its effects on family income inequality in some selected areas of Khulna district - Husna, Asma Ul; Ethen, Dilshad Zahan; Begum, Ismat Ara; Yesmin, Farzana; Khushi, Hurunnahar; Mahfuza, Eshrat Jahan (Research in Agriculture Livestock and Fisheries, 2020)
This study attempted to find out the determinants of shrimp production and to assess the effects of income from shrimp production on family income inequality in Khulna district of Bangladesh. Forty-five farmers were selected from the Bhanderkote union of Batiaghata Upazila under Khulna District. Among them 15 were small farmers, 22 were medium farmers and 8 were large farmers. Data were collected from May to July 2014 through face to face interview. Ordinary Least Square had been used to find out the determinants of shrimp production. Gini coefficient was measured to see the effects of family income inequality. Expenditure on shrimp fingerling, feed, lime, education, and hired labor were the important determinants and had significant effects on shrimp production. Shrimp farm incomes were equal among all categories of farmers (small, medium and large) and all farmers bear the value of Gini0.31, 0.24, 0.12 and 0.36 respectively. In the case of nonfarm incomes small, large and all farmers were relatively equal (G=0.49, G=0.42, and G=0.44 respectively) where the medium farmers (G=0.55) were relatively unequal. Res. Agric., Livest. Fish.7(1): 153-163, April 2020